Gender Dynamics, Workload, and Job Satisfaction: Understanding Employee Motivation and Operational Failures at PT BRT - Elita Arya Maharani Marjuk; Andika Putra Pratama (Universitas Pahlawan Tuanku Tambusai, 2026)
The institutional catering industry depends heavily on human resources to maintain service quality and operational reliability. PT Boga Rasa Tama (PT BRT) has experienced recurring client complaints, employee turnover, and stagnant business performance, indicating underlying organizational challenges related to employee management. A qualitative single-case study design was employed using semi-structured interviews with seven purposively selected informants representing management, HRGA, supervisors, and operational employees, complemented by analysis of internal company documents. Data were analyzed using Braun and Clarke's six-phase thematic analysis and validated through methodological triangulation. The findings identified seven interconnected themes: gender dynamics, psychological safety, structural workforce insufficiency, recognition gap, family culture, kitchen–service communication breakdown, and the absence of formal human capital systems. Cross-theme analysis revealed that the lack of structured training, performance measurement, and recognition systems constituted the fundamental organizational condition underlying operational failures. Informal gender-based task allocation, excessive workload, weak psychological safety, and communication problems collectively reduced employee motivation and service reliability, while the family culture helped retain employees without resolving structural deficiencies. Strengthening formal human capital management systems is therefore essential for improving employee motivation, operational consistency, and long-term organizational performance in institutional catering companies.